Penemuan Awal BerkaitanPemuliharaan Bandar dalam Pembentukan ImejBandar di Tanjong Malim, Perak: Preliminary Urban Conservation Findings of Tanjong MalimImage Development - Saleh, Yazid; Hashim, Mohmadisa; Che Ngah, Mohamad Suhaily Yusri; Nayan, Nasir (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2011)
Urban conservation is one aspect that has been emphasised in urban planning. This effort is done to maintain the image of a city or state to preserve its culture. Generally, conservation processed need efforts such as treatment according to certain conditions, including maintenance, rehabilitation, reconstruction and reconciliation. In this case, the town of Tanjong Malim which can be considered as an old town established since the British colonial era while it became famous with the establishment of the Sultan Idris Training College (SITC) in 1922. In terms of architecture, there are several buildings in the town has a heritage value that can be maintained and preserved. Thus, conservation and image of the city has a very strong relationship because through physical improvements on urban conservation, their image can be highlighted. Early findings in Tanjong Malim town shows there is no attempt beingmade by the responsible parties in terms of preserving some of the heritage buildings to maintained images of Tanjong Malim. Although Tanjong Malim also known as a city of education, research shows no one has tried to capture the uniqness of the city in order to retain or enhance their image. Cooperation of local authorities, urban planners departments and universities required to jointly assess and make appropriate plans for the conservation of Tanjong Malim town.